WEAR RESISTANCE OF LASER CLADDING NiCrBSi COMPOSITE COATINGS - Hulka, Iosif; Şerban, Viorel Aurel; Uțu, Dragoș; Duțeanu , Narcis Mihai; Pascu, Alexandru; Roata, Ionut Claudiu; Maior, Ioana (Romanian Journal of Materials, 2016)
Laser cladding NiCrBSi composite coatings were deposited on the surface of stainless steel substrates using different scanning speeds. The influence of scanning speed on dilution rate and the coatings microstructure were investigated by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX) and X-ray diffraction. Analysis of microhardness, porosity and the wear behaviour of the obtained coatings were revealed. The coatings were analysed and finally compared to each other. It was found that the microstructure and wear resistance of the coatings were influenced by the scanning speed and dilution.
Keywords: aser cladding; coatings; wear resistance